2000
DOI: 10.1093/oxfordjournals.aje.a010235
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cortical, Nuclear, and Posterior Subcapsular Cataracts: The POLA Study

Abstract: The POLA (Pathologies Oculaires Liées à L'Age) Study is a population-based study of cataract and age-related macular degeneration and their risk factors being carried out among 2,584 residents of Sète, southern France, aged 60-95 years. Recruitment took place between June 1995 and July 1997. Cataract classification was based on a standardized lens examination by slit lamp, according to Lens Opacities Classification System III. This paper presents results obtained from cross-sectional analysis of the first phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
162
3
18

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(199 citation statements)
references
References 38 publications
15
162
3
18
Order By: Relevance
“…Several new reports have been published on the risk factors associated with the prevalence of cataracts since the last major reviews, confirming previously identified associations for smoking, 23,34,36,37 diabetes, 34,[38][39][40][41] and UV-B exposure, 23,34,36,[42][43][44][45] and indicating new associations that would need further explorations. 23,32,34,36,[38][39][40]46 Thus, more attention has been paid to systemic diseases and the use of medications.…”
Section: Recent Reportssupporting
confidence: 69%
See 1 more Smart Citation
“…Several new reports have been published on the risk factors associated with the prevalence of cataracts since the last major reviews, confirming previously identified associations for smoking, 23,34,36,37 diabetes, 34,[38][39][40][41] and UV-B exposure, 23,34,36,[42][43][44][45] and indicating new associations that would need further explorations. 23,32,34,36,[38][39][40]46 Thus, more attention has been paid to systemic diseases and the use of medications.…”
Section: Recent Reportssupporting
confidence: 69%
“…23,32,34,36,[38][39][40]46 Thus, more attention has been paid to systemic diseases and the use of medications. An increased risk of cortical cataract prevalence was associated with the use of amiodarone, 46 gout duration of greater than 10 years, arthritis and the use of oral beta-blockers, 23,34 weight change, and use of thyroid hormones.…”
Section: Recent Reportsmentioning
confidence: 99%
“…We found that the age-and sex-adjusted RR of dying in diabetic patients on insulin treatment was 2.7 (95% CI 1.7-4.4) after the 5-year follow-up. Several studies have shown diabetes is a risk factor for both cortical and posterior subcapsular cataract (26,27). Cortical cataract is a frequent type of agerelated cataract, and in this study advanced cortical cataract affected 6% of the subjects, whereas advanced posterior subcapsular cataract affected Ͻ2%.…”
Section: Methodsmentioning
confidence: 46%
“…Estimates of age-adjusted odds ratios (ORs), 95% confidence intervals (95%CIs) and linear trend of foods and beverages for prostate cancer were calculated by conditional logistic regression models with adjustment for cigarette smoking and total energy intake as potential confounding factors. Because some controls were selected from patients with smoking-related diseases, such as cataracts 10,11) and oral diseases, [12][13][14] we adjusted for cigarette smoking in the analyses. Energy adjustment was performed by a logistic regression model that used total energy as a confounding factor, since food groups were analyzed instead of nutrients in this report.…”
Section: Subjectsmentioning
confidence: 99%